Evaluation of retinal nerve fibre layer and macular thickness pre-and post-chemotherapy with carboplatin and paclitaxel in patients with endometrial and ovarian cancer - Juen, Chin Ju (2021)
Background Carboplatin and paclitaxel are two standard chemotherapeutic agents known to cause neurotoxicity. In this study we aim to evaluate the toxicity by measuring the peripapillary retinal nerve fibre layer (RNFL) and macular thickness in patients with endometrial and ovarian cancers receiving them. Methods A one-year prospective cohort study involving 28 patients who were treated intravenously with carboplatin (200-400mg/m2) and paclitaxel (175mg/m2) three-weekly for 6 cycles was conducted. RNFL and macula thickness were measured using optical coherence tomography (OCT) before commencement of chemotherapy, after the third cycle, and one month after the sixth cycle. The main outcome measurements were the average RNFL thickness and central subfield thickness of macula. Results The mean age of the 28 participants was 54.68 years old (SD=9.03). Eleven had endometrial cancer while 17 had ovarian cancer. The mean of the average RNFL thickness during baseline pre-chemotherapy was 96.43μm (SD 11.39). One month after cessation of treatment the mean RNFL thickness increased to 101.57μm (SD 13.54). Statistical analysis showed a significant increment in the mean RNFL thickness (p=<0.001), from baseline to after three cycles, and baseline to one-month post six cycles of chemotherapy, except nasal quadrant. The increment in all the macular quadrants was statistically significant (p < 0.05) except central subfield thickness. Conclusion Systemic administration of carboplatin and paclitaxel affected both the peripapillary RNFL and macula thickness. This represents early evidence of subacute subclinical retinal toxicity. OCT can be used as a screening tool to assess peri-chemotherapeutic retinal alterations.